2016
DOI: 10.1177/1077546316667323
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of global and targeted control of walkway bridge resonant frequencies

Abstract: In this paper, three controllers are investigated for active vibration control (AVC) of a pedestrian walkway structure. They comprise of direct velocity feedback (DVF), observer-based and independent modal space (IMSC) controllers that are implemented in single-input single-output (SISO), multi-SISO and multiple-input multiple-output (MIMO) configurations. The objective of the SISO controller schemes is to compare vibration mitigation performances arising from global control versus selective control of structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Therefore, the control force for multiple modes, denoted by f()t, is calculated by f()tgoodbreak=f1()tgoodbreak+f2()tgoodbreak+f3()tgoodbreak+goodbreak=()goodbreak−β10.25emq̇1()tgoodbreak+()goodbreak−β20.25emq̇2()tgoodbreak+()goodbreak−β30.25emq̇3()tgoodbreak+ The response reduction effect for each mode is achieved by choosing a sufficiently large value of the control gain βj. However, it has been shown that the use of an actuator introduces a pair of high‐damped poles that substantially affect the dynamic property of the structural system 11,28 . Since the dynamics of the actuator or other involved components are not negligible in the whole control system, reduction of the modal response 0.25emq̇j()t would be different depending on the mode j .…”
Section: Active Control Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the control force for multiple modes, denoted by f()t, is calculated by f()tgoodbreak=f1()tgoodbreak+f2()tgoodbreak+f3()tgoodbreak+goodbreak=()goodbreak−β10.25emq̇1()tgoodbreak+()goodbreak−β20.25emq̇2()tgoodbreak+()goodbreak−β30.25emq̇3()tgoodbreak+ The response reduction effect for each mode is achieved by choosing a sufficiently large value of the control gain βj. However, it has been shown that the use of an actuator introduces a pair of high‐damped poles that substantially affect the dynamic property of the structural system 11,28 . Since the dynamics of the actuator or other involved components are not negligible in the whole control system, reduction of the modal response 0.25emq̇j()t would be different depending on the mode j .…”
Section: Active Control Frameworkmentioning
confidence: 99%
“…However, it has been shown that the use of an actuator introduces a pair of high-damped poles that substantially affect the dynamic property of the structural system. 11,28 Since the dynamics of the actuator or other involved components are not negligible in the whole control system, reduction of the modal response _ q j t ð Þ would be different depending on the mode j. It is often the case that the phase change caused by the actuator dynamics degrades the performance of the control strategy by the resulting decrease of the stability margin as well as the reduction of damping introduced by the active control system.…”
Section: Concept Of Mdvf Control Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the investigated vibrational behavior of the cables and bridges, it is the engineering concern to control the vibration and dynamic responses of bridges. Numerous research studies have been carried out in this field such as using inclined suspenders (VGTU Report, 2003) or vibration and resonant frequency controllers (Caetano et al, 2010; Liu et al, 2010; Nyawako and Reynolds, 2016; Zhang et al, 2019). Among the structural control solutions, using dampers to reduce the vibration of cables and bridges has been an efficient method.…”
Section: Introductionmentioning
confidence: 99%